2019
DOI: 10.1186/s10194-019-0991-2
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and episodic Vertigo: a cohort survey study of their relationship

Abstract: Background and aimMigraine headache and vestibular-type vertigo co-occur in the general population about three times more often than expected by chance. Attacks of episodic vertigo (eV) are currently not recognized as migraine equivalents or variants in the International Classification of Headache Disorders, 3rd edition (ICHD III). No strong data exist about the prevalence of eV during the phases of a migraine attack. The aim of this study is to analyze the timing association between migraine-related episodic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 21 publications
2
35
0
1
Order By: Relevance
“…Our study suggests that migraineurs with vestibular symptoms exhibit similar postural control than migraineurs without self-report of vestibular symptoms. Additionally, we verified a high prevalence of the vestibular symptoms among the patients, which agrees with previous findings [1][2][3][4][5][6][7][8][9][10][11]. Based on the present and previous findings, we suggest that the vestibular symptoms and balance changes are a common condition among migraineurs and may be present on different severity levels according to the classic clinical presentation of migraine; and not due to a different classification considering only the presence of vestibular symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study suggests that migraineurs with vestibular symptoms exhibit similar postural control than migraineurs without self-report of vestibular symptoms. Additionally, we verified a high prevalence of the vestibular symptoms among the patients, which agrees with previous findings [1][2][3][4][5][6][7][8][9][10][11]. Based on the present and previous findings, we suggest that the vestibular symptoms and balance changes are a common condition among migraineurs and may be present on different severity levels according to the classic clinical presentation of migraine; and not due to a different classification considering only the presence of vestibular symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Migraineurs present a high prevalence of vestibular symptoms, such as dizziness and vertigo [1][2][3][4][5][6][7][8][9][10]. The cooccurrence of these symptoms with migraine is more frequent than expected by chance [10,11] during both the ictal and interictal period [6,9], and it can augment the impact on migraineurs' quality of life [1,4]. In that way, these symptoms can be considered as either part of the migraine presentation [11] or a different classificationas described in the Appendix of the International Classification of Headache Disorders (ICHD-III) as vestibular migraine [12], which was jointly formulated with the Committee for Classification of Vestibular Disorders of the Bárány Society [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This link has been demonstrated in rats [ 68 ]. In addition, it has been suggested that an imbalance of the vestibular system may be induced by a painful trigeminal stimulation in migraine patients [ 18 ], and some authors have proposed that a vestibular disorder should be considered as an integral manifestation of headache and not as two different and concomitant diseases [ 69 ]. The function of the vestibular pathways is crucial in SVV perception.…”
Section: Discussionmentioning
confidence: 99%
“…The cortex and vomiting center in the brainstem are influenced by various extrinsic factors, including movement (via the vestibular system), drugs (such as opioids and anesthetics), activity in the area postrema, intestinal vagal afferent fiber activity and pain (in association with surgical manipulation of the gut), and emotions during the perioperative period (mediated by higher cortical centers) [ 34 ]. Migraine is associated with a wide range of psychiatric comorbidities, as well as various vestibular symptoms and vestibular syndromes [ 58 , 59 , 60 , 61 ]. The pain experienced by migraine sufferers, and the accompanying symptoms such as dizziness, vertigo, and anxiety, are likely to affect the development of PONV.…”
Section: Discussionmentioning
confidence: 99%